Infant Mortality Categorized by Birth Weight Percentiles for Deliveries between 22 and 28 Weeks of Gestation - Onishi, Kazuma; Bitas, Christiana; Kawakita, Tetsuya (American Journal of Perinatology, 2024)
Objective Our objective was to describe infant mortality within 1 year of life according to gestational age and birth weight percentile in infants delivered between 22 and 28 weeks of gestation.Study Design This study was a retrospective cohort study based on publicly available U.S. birth certificate data linked to infant death data between 2014 and 2020. Maternal–neonate pairs of singleton live births between 220/7 and 286/7 weeks' gestation (vaginal or cesarean) were evaluated. We excluded infants with major fetal anomalies, chromosomal disorders, and birth weight outliers. Our primary outcome was infant mortality within 1 year of life. Individuals were categorized into eight sex-specific birth weight percentiles categories: less than the 3rd, 3rd-less than the 10th, 10th-less than the 25th, 25th-to less than the 50th, 50th-less than the 75th, 75th-to less than the 90th, 90th-less than the 97th, and 97th or higher.Results Of 27,014,444 individuals with live births from January 2014 to December 2020, 151,677 individuals who gave birth at 22 to 28 weeks of gestation were included in the study population. The mortality rate ranged from 4.2% for the 50th-less than the 75th percentiles at 28 weeks to 80.3% for the 3rd-less than the 10th percentile at 22 weeks. Using the 50th-less than the 75th birth weight percentile at each gestational age as a reference group, birth weight less than the 50th percentile was associated with increased mortality at all gestational ages in a dose-dependent manner. From 22 to 25 weeks of gestation, higher birth weight percentiles were associated with lower mortality, while the 97th or higher birth weight percentile was associated with increased mortality compared with the 50th-less than the 75th birth weight percentile at 26 to 28 weeks of gestation.Conclusion The lower birth weight percentiles were associated with higher mortality across all gestational ages, but the association between higher birth weight percentiles and infant mortality exhibited an opposite pattern at 22 to 25 weeks as compared to later gestational age.Key Points
Keywords: extremely preterm; fetal surveillance; large for gestational age; Infant mortality preterm birth; small for gestational age